(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Transmission Electron Microscopy (TEM) is an important scientific imaging technique; however, students often find its underlying principles difficult to understand because of the abstract nature of electron optics and the limited availability of microscopy equipment in educational settings. This study developed and evaluated a low-cost Single-Point Optical Scanning Instructional System designed to demonstrate the fundamental principles of TEM through hands-on and visualization-based learning. The prototype utilized a laser module, optical sensors, stepper motors, a turntable mechanism, an Arduino Uno microcontroller, and image reconstruction software to simulate scanning, signal detection, and image formation processes. A mixed-methods project-based research design was employed involving ten Grade 12 STEM students. Participants completed pre-test and post-test assessments to measure conceptual understanding before and after exposure to the instructional demonstration. Results showed an increase in mean scores from 8.20 to 12.40, representing a 51.22% improvement. A paired-samples t-test indicated that the increase was statistically significant, t(9) = 8.20, p < 0.001. The findings suggest that the developed instructional system effectively improves students’ understanding of TEM principles while providing an affordable alternative to expensive microscopy equipment. The study highlights the potential of low-cost, interactive STEM instructional tools for enhancing science education in resource-limited learning environments.